Pengaplikasian Program Vitamin Ternak TeBing (Temulawak Kambing) di Desa Kalisat Kecamatan Ijen Kabupaten Bondowoso - Akhmad Munif Mubarok; Liza Ayu Dwi Kharisma; Mahega Cindya Firliyanti; Achmad Ismail; Yusnan Hadi Mochtar; Kurniawati Sa’adah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Goat farming in Kalisat Village continues to face issues regarding low productivity due to traditional husbandry practices and a lack of nutritional supplementation. This community service program in Kalisat Village, Ijen District, Bondowoso Regency, aimed to improve goat health and productivity through the implementation of